2008
DOI: 10.1111/j.1349-7006.2007.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic value of p53 mutation spectra and differences with histology in lung cancers

Abstract: A total of 297 resected Japanese non-small cell lung cancers (74 squamous cell carcinomas and 223 adenocarcinomas) were analyzed to evaluate the validity of the p53 mutation spectrum as a fingerprint for mutagenic substances as etiological factors. Frequencies of G→ → → →T transversions in smokers were significantly higher than in non-smokers (P = 0.003) and the average incidence of G→ → → →T at hot spot codons of adduct formation was higher than that in other codons in smokers and in the hot spots in non-smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The combined approach of DHPLC and DNA sequencing analysis revealed that of the 105 cases, 1 (1%, 95% confidence interval 0.02-5.2) carried a deleterious TP53 frame shift mutation in exon 5, c.499-500delCA. This germ line mutation was previously reported as a somatic mutation in four other cancer types [28][29][30][31], but it is the first incidence of it occurring in the germ line (Table 1). It was found in a 28-year-old early-onset breast cancer patient of Punjabi ethnicity with no family history of breast or ovarian cancer.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The combined approach of DHPLC and DNA sequencing analysis revealed that of the 105 cases, 1 (1%, 95% confidence interval 0.02-5.2) carried a deleterious TP53 frame shift mutation in exon 5, c.499-500delCA. This germ line mutation was previously reported as a somatic mutation in four other cancer types [28][29][30][31], but it is the first incidence of it occurring in the germ line (Table 1). It was found in a 28-year-old early-onset breast cancer patient of Punjabi ethnicity with no family history of breast or ovarian cancer.…”
Section: Resultsmentioning
confidence: 77%
“…This is the first report of this mutation being identified in the germ line. Previously, it was reported as a somatic mutation in four patients with other cancer types: a women from Kashmir valley (Indian part) diagnosed with esophageal squamous cell carcinoma at age 50 [31], a Japanese male diagnosed with adenocarcinoma of the lung at age 60 [28], a German women diagnosed with squamous cell carcinoma of larynx at age 46 [29] and a male patient from the US diagnosed with adenocarcinoma of the descending/sigmoid colon at 61 years of age [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a number of studies have shown that TP53 gene mutations are more common in lung cancers from smokers than they are in lung cancers from never smokers, and, again, the G:C to T:A transversions predominate with a specificity towards CpG sites [14, 17, 23–25]. Thus, there is a strong “fingerprint” of tobacco carcinogens in the DNA of lung cancer [24, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer, many p53 mutations are located in CpG-rich regions that have a significant proportion of transitions [27,28]. Cancerous lungs of smokers have revealed both transversions and transitions in p53 [29], which may in part be a result of the oxidants generated in tar and the RNS in smoke. In contrast, in the cancerous lungs of non-smokers transitions are more prominent, suggesting that inflammation favors transitions.…”
mentioning
confidence: 99%